Caught in speciation? A new host for Conchodytes meleagrinae Peters, 1852 (Decapoda, Caridea, Palaemonidae) - Fransen, Charles H.j.m.; Reijnen, Bastian T. (Zootaxa, 2013)
During fieldwork in 2009 at Ternate, Indonesia, a pair of a pontoniine shrimp species belonging to the genus Conchodytes was collected from a bivalve mollusk of the genus Spondylus. This constitutes the first record of a species of the genus Conchodytes associated with a spondylid host. The specimens can be distinguished from other known Conchodytes species based on both morphology and colour pattern. Its COI barcode however, strongly resembles those obtained from three specimens of C. meleagrinae and is nested in the C. meleagrinae clade of the reconstructed phylogeny. Based on morphology and colouration only the specimens associated with the Spondylus bivalve would have been described as a species new to science. The modest conflicting molecular data have lead the authors to fully describe and figure the Spondylus associated specimens and compare them with the Pinctada associated specimens. Based on the present information it is decided not to give the Spondylus associated specimens the status as a distinct species but regard them as host-related (colour)morph of Conchodytes meleagrinae.